Rambu Solo dan Ekologi: Manfaat Studi Biblika Kontekstual dalam Membangun Spiritualitas Ekoteologi di Toraja - Yakobus Komura (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Humans and nature are an inseparable unity, as determined by God to establish harmony. Ecological relations that should be reciprocal are not visible, due to human behavior which tends to be anthropocentric towards nature. The rise of the ecological crisis forces Christianity to continue to rethink its role in promoting ecological conversion, especially in Toraja, which is predominantly Christian, which is also rich in customs and culture. The wealth that has made it increasingly known throughout the earth has now forgotten the awareness of the balance of its ecosystem. In particular, the Rambu Solo' culture is a funeral (death) rite or ceremony among the Toraja people who have certain levels based on their social strata, which then consumes a lot of natural attributes including animal sacrifices. Based on this concern, the role of contextual biblical studies is considered important in building awareness of ecological spirituality to become a bridge in maintaining ecosystem balance. Awareness to see others as creations that give each other life. The method in this paper attempts to use a synthetic or dialogical model. The synthetic model is a model that appears serious in involving other contexts.ABSTRAKManusia dan alam adalah satu kesatuan yang tak terpisahkan, sebagaimana yang ditetapkan oleh Allah untuk menjalin keharmonisan. Relasi ekologi yang semestinya bersifat timbal balik tidak nampak, akibat perilaku manusia yang cenderung antroposentris terhadap alam. Maraknya krisis ekologis memaksa kekristenan untuk terus memikirkan kembali peranannya dalam menggemakan pertobatan ekologis, khususnya di Toraja yang mayoritas agama Kristen, yang juga kaya akan adat dan budayanya. Kekayaan yang membuatnya makin dikenal hingga penjuru bumi, kini lupa akan kesadaran keseimbangan ekosistemnya. Khususnya budaya Rambu Solo’ yang merupakan ritus atau upacara pemakaman (kematian) dikalangan masyarakat Toraja yang memiliki tingkatan-tingakatan tertentu berdasarkan strata sosialnya, yang kemudian banyak menghabiskan atribut alam termasuk kurban hewan. Atas dasar keprihatinan ini maka dipandang penting peranan studi biblika kontekstual untuk membangun kesadaran spiritualitas ekologi menjadi jembatan dalam menjaga keseimbangan ekosistem. Kesadaran untuk melihat yang lain sebagai ciptaan yang saling memberi kehidupan. Metode dalam tulisan ini mengupayakan dengan menggunakan model sintesis atau dialogis. Model sintesis ialah model yang nampak serius dalam melibatkan konteks-konteks yang lain. Kata-kata kunci: Biblika, Ekoteologi, Rambu Solo’, Spiritualitas, Toraja